The relationship between output And unemployment in Malaysia: does Okun’s Law exist? - Mohd Noor, Zaleha; Mohamed Nor, Norashidah; Abdul Ghani, Judhiana (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
Unemployment is an important issue in developing economies. High unemployment means that labour resources are not being used efficiently. In the macroeconomic framework there is a well known relationship called Okun’s Law, which states that the negative relationship between movements of unemployment rate and real GDP can be determined. This paper examines whether there exist an Okun-type relationship between output and unemployment in the Malaysian economy. The empirical results show that the negative relationship between output and unemployment is present. Some policy implications are discussed at the end of the paper.